GELIAT PENULISAN KITAB HADIS DI PESANTREN (Stu di Kit Ã„Âb FadlÃ„Âil al -Taha jjud wa QiyÃ„Âm al -Lail Karya Ahmad Yasin bin Asmuni) - Muhtaruddin, M. Bik (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2018)
It cannot be denied that the activity of hadith study in pesantren is not as popular as others studies as like tafsir and fiqh. Since the less attention on the hadith study, the Indonesian scholarsÃ¢â‚¬â„¢ (ulama) work especially pesantren scholars on hadith is very limited. Moreover, the contemporary scholars do not have the similar works. This article discusses a book Ã¢â‚¬Å“Fad}a>il al-Tahajjud wa Qiya>m al-LailÃ¢â‚¬Â as one of works from pesantren Hidayatut Thullab, Petuk, Kediri regency. This book has some significance. First, the book Ã¢â‚¬Å“Fad}a>il al-Tahajjud wa Qiya>m al-LailÃ¢â‚¬Â is a summary of hadith, athar, and ulamaÃ¢â‚¬â„¢s speech about the importance of tahajjud praying riwayah from Abi> Dunya. Second, the quality of the hadith in this book is less attention, since the purpose of book arrangement is to motivate communities to have spirit in doing tahajjud and qiya>m al-lail. Third, the book Ã¢â‚¬Å“Fad}a>il al-Tahajjud wa Qiya>m al LailÃ¢â‚¬Â was arranged from communitiesÃ¢â‚¬â„¢ need to have a clear guide, either from hadith or others. Keywords: Hadith, pesantren, book Fad}a>il al-Tahajjud wa Qiya>m al-Lail.